2017
DOI: 10.1007/s10557-017-6757-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vascular Disease Treatment on Platelet-Derived Microvesicles

Abstract: Platelet-derived microvesicles (pMVs) are small, heterogeneous vesicles released from platelet membranes as a result of activation. These microvesicles possess a wide range of properties, including prothrombotic, proatherogenic, proinflammatory, immunomodulatory, and even anticoagulant activity. The elevated release of these microvesicles has been observed in various metabolic, inflammatory, thrombotic, and vascular diseases, including ischemic heart disease, stroke, hypertension, diabetes, and connective tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 143 publications
(184 reference statements)
0
60
0
1
Order By: Relevance
“…Notably, an ex vivo study demonstrated that about 23-40% of the procoagulant activity of human platelet suspensions appeared associated with PMVs 11. Besides providing an additional anionic surface for coagulation, including procoagulant activity at a distance from the site of platelet activation, PMVs have been implicated in pro-inflammatory and pro-atherosclerotic effects 10,12-14. Elevated numbers of plasma PMVs were described in patients with clinical atherosclerotic CV disease or risk factors, which has been linked to chronic platelet activation 10,12.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, an ex vivo study demonstrated that about 23-40% of the procoagulant activity of human platelet suspensions appeared associated with PMVs 11. Besides providing an additional anionic surface for coagulation, including procoagulant activity at a distance from the site of platelet activation, PMVs have been implicated in pro-inflammatory and pro-atherosclerotic effects 10,12-14. Elevated numbers of plasma PMVs were described in patients with clinical atherosclerotic CV disease or risk factors, which has been linked to chronic platelet activation 10,12.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension was the only risk factor used in the adjusted model because a significant difference in hypertension was observed between the NSTEMI and STEMI groups among the study subjects. It has been reported that levels of MPs were decreased by the effect of some vascular disease medications including statin, ACEI/ARB, aspirin, and clopidogrel [31]. Although the study subjects had taken these drugs, the proportion of NSTEMI and STEMI patients who were treated with these medications was not significantly different.…”
Section: Discussionmentioning
confidence: 81%
“…Although there is strong interrelation between endothelial dysfunction in hypertension and spontaneous generation of platelet-derived vesicles, whether tight control for blood pressure will correspond to a significant decrease of platelet aggregation and reducing the number of circulating pro-coagulant platelet-derived vesicles is not fully understood [62] . However, diminishing of pro-coagulant activity of circulating platelet-derived vesicles can be achieved during effective antihypertensive therapy [62][63][64] . It has been noted that a wide range of antihypertensive drugs, such as calcium channel blockers, angiotensin-II receptor antagonists, angiotensin-converting enzyme inhibitors, are able to hamper the process of micro vesiculation and thereby to reduce a circulating number of platelet-derived vesicles [63,64] .…”
Section: Platelet-derived Vesicles In Hypertensionmentioning
confidence: 99%
“…However, diminishing of pro-coagulant activity of circulating platelet-derived vesicles can be achieved during effective antihypertensive therapy [62][63][64] . It has been noted that a wide range of antihypertensive drugs, such as calcium channel blockers, angiotensin-II receptor antagonists, angiotensin-converting enzyme inhibitors, are able to hamper the process of micro vesiculation and thereby to reduce a circulating number of platelet-derived vesicles [63,64] . Taken into consideration the role of the vesicles in the pathogenesis of hypertension a variable ability of several antihypertensive drugs to modify shaping and releasing of the particles onto circulation is showed to have promising and require more investigations in the future.…”
Section: Platelet-derived Vesicles In Hypertensionmentioning
confidence: 99%